Complement activation and endothelial perturbation parallel COVID-19 severity and activity. Issue 116 (January 2021) - Cugno, Massimo; Meroni, Pier Luigi; Gualtierotti, Roberta; Griffini, Samantha; Grovetti, Elena; Torri, Adriana; Lonati, Paola; Grossi, Claudia; Borghi, Maria Orietta; Novembrino, Cristina; Boscolo, Massimo; Uceda Renteria, Sara Colonia; et al.
Abstract: Background: Animal models and few clinical reports suggest the involvement of the complement system in the onset of severe manifestations of coronavirus disease-2019 (COVID-19). However, complement contribution to endotheliopathy and hypercoagulability has not been elucidated yet. Objective: To evaluate the association among complement activation, endothelial damage and disease severity or activity in COVID-19 patients. Methods: In this single-centre cohort study, 148 patients with COVID-19 of different severity were evaluated upon hospital admission and 30 days later. Markers of complement activation (SC5b-9 and C5a) and endothelial perturbation (von Willebrand factor [vWF], tissue-type plasminogen activator [t-PA], plasminogen activator inhibitor-1 [PAI-1], soluble thrombomodulin [sTM], and soluble endothelial selectin [sE-selectin]) were measured in plasma. Results: The patients had high plasma levels of SC5b-9 and C5a (p = 0.0001 for both) and vWF, t-PA and PAI-1 (p = 0.0001 for all). Their SC5b-9 levels correlated with those of vWF (r = 0.517, p = 0.0001) and paralleled disease severity (severe vs mild p = 0.0001, severe vs moderate p = 0.026 and moderate vs mild p = 0.001). The levels of sE-selectin were significantly increased only in the patients with severe disease. After 30 days, plasma SC5b-9, C5a and vWF levels had significantly decreased (p = 0.0001 for all), and 43% of the evaluated patients had normal levels. Conclusions: Complement activation is boosted during the progression of COVID-19 and dampened during remission, thus indicating its role in the pathophysiology of the disease. The association between complement activation and the biomarkers of endothelial damage suggests that complement may contribute to tissue injury and could be the target of specific therapy. Highlights: Levels of complement activation products increase with COVID19 severity and activity. Complement activation is correlated with endothelium damage in COVID19. Complement mediates the response to SARSCoV2 and gives a rationale for target therapy.